Interleukin‐9 Overexpression and Th9 Polarization Characterize the Inflamed Gut, the Synovial Tissue, and the Peripheral Blood of Patients With Psoriatic Arthritis. Issue 8 (27th July 2016) - Ciccia, Francesco; Guggino, Giuliana; Ferrante, Angelo; Raimondo, Stefania; Bignone, Rodolfo; Rodolico, Vito; Peralta, Sergio; Van Tok, Melissa; Cannizzaro, Alessandra; Schinocca, Claudia; Ruscitti, Piero; Cipriani, Paola; et al.
Abstract : Objective: To investigate the expression and tissue distribution of Th9‐related cytokines in patients with psoriatic arthritis (PsA). Methods: Quantitative gene expression analysis of Th1, Th17, and Th9 cytokines was performed in intestinal biopsy samples obtained from patients with PsA, HLA−B27−positive patients with ankylosing spondylitis (AS), patients with Crohn's disease (CD), and healthy controls. Expression and tissue distribution of interleukin‐23 (IL‐23), IL‐17, IL‐22, IL‐9, and IL‐9 receptor (IL‐9R) were evaluated by immunohistochemistry and confocal microscopy. Flow cytometry was used to study the frequency of Th9 cells among peripheral blood, lamina propria, and synovial fluid mononuclear cells. The functional relevance of IL‐9R expression on epithelial cells was assessed in functional in vitro studies. Th9 cells in synovial tissue from patients with PsA were also studied. Results: Subclinical gut inflammation in PsA patients was characterized by a clear Th17 and Th22, but not Th1, polarized immune response. Unlike AS and CD, a strong and significant up‐regulation of IL‐9 was observed in PsA gut, especially among infiltrating mononuclear cells, high endothelial venules, and Paneth cells. IL‐9−positive mononuclear cells were demonstrated to be in large part Th9 cells. IL‐9 overexpression was accompanied by significant Paneth cell hyperplasia. Paneth cells strongly overexpressed IL‐9R, and stimulation of epithelial cells, isolated from PsA patients, with IL‐9 resulted in overexpression of α‐defensin 5 and IL‐23p19. Peripheral and synovial expansion of α4β7+ Th9 cells was also observed in patients with PsA. Increased expression of IL‐9 and IL‐9R was also found in synovial tissue. Conclusion: Strong IL‐9/Th9 polarization seems to be the predominant immunologic signature in patients in PsA.